The evolution of types of saints from the Middle Ages until the Modern Era - N.I. Egorov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper considers whether it is possible and appropriate to differentiate between the types of saints in the Middle Ages and the early Modern Era in Europe. The study is based on the analysis of various types of sources, such as saints’ lives, protocols of canonization processes, and other church acts. The typologies of “old” (late antique and medieval) and “new” (represented by the so-called beati moderni) saints were compared. The differences between the medieval and the modern vision of sanctity in Catholic Church were revealed. The classifications of saints proposed by A. Voshe and M.Yu. Paramonova were discussed. A new classification of beati moderni was suggested. The specifics of canonization of “new saints” and the phenomenon of their emergence were explored. Using the results of the comparative analysis, it was concluded that “new saints” must be distinguished from the medieval ones, because they are a reflection of the realities and values of the early Modern Era. In many cases, they determined a new image of saints in Catholic Church, which has been common since the Council of Trent until the present times.